SOCIAL PRESSURE AMONG FORMER DRUG ADDICTSAFTER DISCHARGED FROM DRUG REHABILITATION CENTRE - Ibrahim, Fauziah (International Journal of Psychosocial Rehabilitation, 2020)
Social pressure could influenceindividualsto recover from drug addiction. The purpose of this study is to identify the levels of social pressure among former drug addicts and to identify the influence of internal and external factors on social pressure among the former addicts. The study was carriedoutusing a quantitative cross-sectional design. A total of 380 former drug addicts who completed the rehabilitation programmes at Cure and Care Rehabilitation Center (CCRC) and undergoing supervision orders by the National Anti-Drugs Agency were selected to participate in this study. The data wereanalysed using both descriptive and inferential statistics, includingmultiple regression and stepwise tests.The findings of the study showing that the majority of former drug addicts involved in this study reported low (48.9%) and moderate (47.1%) levels of social pressure. In the regression analysis,predictorssuch as drug craving (β=.436,p